THE APPLICATION OF AUDIO-VISUAL MEDIA IN OPTIMIZING THE LEARNING OUTCOMES OF GRADE III STUDENTS IN THEMATIC LEARNING AT MUHAMMADIYAH PK KOTTABARAT ELEMENTARY SCHOOL IN SURAKARTAA - Risqiyanti, Hesti; Fathoni, Achmad (Jurnal Ilmiah Didaktika, 2024)
This research discusses the implementation of audio visual media in thematic learning at SD Muhammdiyah Kottabarat Special Program Surakarta. Descriptive qualitative method was used to describe the implementation of audio visual media and its impact on the learning outcomes of grade 3 students. Data were obtained through in-depth interviews, observation, and documentation. The results showed that before using audio visual media, thematic learning tended to be less conducive and less motivating for students. After the application of audio visual media, there were positive changes in students' enthusiasm, focus, and understanding. The utilization of this media allows teachers to explain the material in detail and attract students' interest. Analysis of pretest and posttest scores showed a very significant increase, with the presentation of students who exceeded the Minimum Completion Criteria (KKM) increased. This study concludes that the use of audio-visual media in thematic learning can improve the effectiveness and learning outcomes of students.